2002
DOI: 10.1128/jvi.76.16.8276-8284.2002
|View full text |Cite
|
Sign up to set email alerts
|

Favorable and Unfavorable HLA Class I Alleles and Haplotypes in Zambians Predominantly Infected with Clade C Human Immunodeficiency Virus Type 1

Abstract: The setpoint of viral RNA concentration (viral load [VL]) during chronic human immunodeficiency virus type 1 (HIV-1) infection reflects a virus-host equilibration closely related to CD8؉ cytotoxic T-lymphocyte (CTL) responses, which rely heavily on antigen presentation by the human major histocompatibility complex (MHC) (i.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
126
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(144 citation statements)
references
References 68 publications
15
126
2
1
Order By: Relevance
“…11 The A*02-Cw16 haplotype was associated with high viral load in HIV-1, clade C-infected Zambians. 12 Finally, a study of C282Y homozygous hemochromatosis subjects demonstrated a significant association between the A*02 allele and a lower CD 8 þ T-lymphocyte count. 13 This association was not observed in healthy controls carrying the A*02 allele, indicating that the lower count may be related to a locus in LD with the A*02 allele.…”
Section: Discussionmentioning
confidence: 98%
“…11 The A*02-Cw16 haplotype was associated with high viral load in HIV-1, clade C-infected Zambians. 12 Finally, a study of C282Y homozygous hemochromatosis subjects demonstrated a significant association between the A*02 allele and a lower CD 8 þ T-lymphocyte count. 13 This association was not observed in healthy controls carrying the A*02 allele, indicating that the lower count may be related to a locus in LD with the A*02 allele.…”
Section: Discussionmentioning
confidence: 98%
“…To further evaluate the relationship between the specificity of CD8 ϩ T-cell responses and immune control, we investigated HLA-B*13, a class I allele previously linked with successful immune control (16,36) but for which comprehensive analyses of the CD8 ϩ T-cell response had not been undertaken. The initial study cohort comprised 1212 antiretroviral therapy-naïve adults from Durban, South Africa, with chronic HIV-1 C clade infections.…”
Section: Human Immunodeficiency Virus (Hiv)-specific Cd8mentioning
confidence: 99%
“…The design and conduct of these studies have been described elsewhere (9,18,28). The selection of mostly HIV-1 subtype Cinfected Zambians (n ϭ 423) was based on the availability of HIV-1 RNA measurements.…”
Section: Subjectsmentioning
confidence: 99%
“…Among B58s alleles (all B*57 alleles, B*5801-*5802, and B*1516-*1517) (25). The HLA-B*57 alleles have consistently been associated with a favorable disease course in populations with different HIV-1 viral subtypes and ethnic backgrounds (1,6,11,28,30). However, assessment of the other B58s alleles has been relatively sparse (4,10,14).…”
mentioning
confidence: 99%